"Batmondi" e apocalisse. Attraversamenti devianti e contaminazioni diegetiche (Mantichora. Italian Journal of Performance Studies, 2020)
Postmodernism is born from a subtraction, and therefore it couldn’t be a grief to generate the events that lead a character like Bruce Wayne to become a dark beast, a hero without superpowers, whose weakness is being fearless about his own death. Wayne is disguised like a Zorro – Bat and so Bat-Man has chimerical semblance of a manque detectable in a mythographic guilt, that animates the deeds and he is portrayed by a knight with an erotic ride by the tables of Klaus Janson. The crime takes root into madness and in a kind of embodied disease against which hero fights: «How can be explained the return of a pain to remove? There is only a paradoxical way: the removed does not come from the past but it will be in the future», from a promised apocalypse.